Formal aspects of component software : 13th International Conference, FACS 2016, Besançon, France, October 19-21, 2016, Revised selected papers /: 13th International Conference, FACS 2016, Besançon, France, October 19-21, 2016, Revised selected papers. (2017) - Unknown
No abstract available